Skellig - Almond, David, 1951- (New York : Delacorte Press, 1999)
Unhappy about his baby sister's illness and the chaos of moving into a dilapidated old house, Michael retreats to the garage and finds a mysterious stranger who is something like a bird and something like an angel.